DRINKING WATER POLLUTION IN INDIA - A CHALLENGE FOR HUMAN HEALTH: भारत में पेयजल प्रदुषण - मानव स्वास्थ्य के लिए एक चुनौति - Jain, Anjana (International Journal of Research -GRANTHAALAYAH, 2015)
According to the latest report of the World Health Organization, 7 lakh 83 thousand people die due to polluted water every year in India. The main challenge of the Government of India is to provide clean water to the public. Therefore, in the study presented, an attempt has been made to know why there is pollution of drinking water, what types of diseases are caused by this polluted water, d. An attempt has been made to know its negative effects and pure drinking water treatment. The data and facts have been compiled on a secondary basis. विष्व स्वास्थ संगठन की ताजा रिपोर्ट के अनुसार भारत में प्रतिवर्ष 7 लाख 83 हजार लोग प्रदूषित जल की वजह से मरते है। जनता को साफ पानी पहुचाना भारत सरकार की मुख्य चुनौति है। अतः प्रस्तुत अध्ययन में यह जानने का प्रयास किया गया है कि पेयजल प्रदुषण क्यों होता है घ् इस प्रदूषित जल से किस प्रकार की बीमारियाँ उत्पन्न होती है घ् इसके नकारात्मक प्रभाव एवं शुध्द पेयजल उपचार को जानने का प्रयास किया गया है। आंकड़ो व तथ्यों का संकलन द्वितीयक आधार पर किया गया है।